2014
DOI: 10.5455/2319-2003.ijbcp20141030
|View full text |Cite
|
Sign up to set email alerts
|

Drug utilization review of anticancer drugs in cancer outpatient department of the Government Medical College, Aurangabad

Abstract: Background: To study drug utilization of anticancer drugs in cancer outpatient department (OPD) of Government Medical College, Aurangabad. Methods: Five hundred and twelve prescription records were screened and analyzed as per the study parameters from cancer OPD of Government Medical College and Hospital, Aurangabad. Commonly used anticancer drugs were recorded; furthermore, different types of carcinomas were noted. Results: Age group of patients was in between 30 and 70, 267 were females and 245 were male pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 1 publication
3
3
1
Order By: Relevance
“…Present study shows that the incidence of carcinoma is high in females as compared to that in males (62 females vs. 38 males), Kulkarni et al, also found that the incidence of carcinoma in females is more than that of males and has written about it in his research article. 12 As the risk of cancer increases with age, a similar pattern was seen in our study. A major 58% of patients were above the age of 50 years.…”
Section: Discussionsupporting
confidence: 89%
“…Present study shows that the incidence of carcinoma is high in females as compared to that in males (62 females vs. 38 males), Kulkarni et al, also found that the incidence of carcinoma in females is more than that of males and has written about it in his research article. 12 As the risk of cancer increases with age, a similar pattern was seen in our study. A major 58% of patients were above the age of 50 years.…”
Section: Discussionsupporting
confidence: 89%
“…In our study, Paclitaxel was commonly prescribed chemotherapeutic agent (34%) followed closely by 5-fluorouracil (32%). This was quite similar to the results reported by Kulkarni et al, showing carboplatin followed by paclitaxel [13]. Among the different classes of cytotoxic drugs observed, alkylating agents was the most prescribed class followed by antimetabolites, antitumor antibiotics, and plant alkaloids.…”
Section: Discussionsupporting
confidence: 81%
“…On analyzing the distribution pattern of cancer patients according to gender, the data represented that cancer was more prevalent in females (54%) than males (46%) in the age between 1-80 y. This data was found to be consistent with the observation of female (52.14%) and male (47.85%) as reported by Kulkarni et al, [13]. The greater prevalence of cancer in females can be due to the involvement of their reproductive system which is more susceptible such as cervix, ovary, and breast and occupies the major portion of all other forms of cancer.…”
Section: Discussionsupporting
confidence: 80%
“…Cytotoxic drugs have a narrow therapeutic index (TI) and the dosage needed to achieve the therapeutic effect would also cause severe toxic effects. 16 In present study, most commonly prescribed anti-cancer drug is cisplatin followed by 5-flurouracil and this is inconsistent with the findings of Mugada et al and Kulkarni et al 9,14 Cisplatin's major side effect is nephrotoxicity. Here cisplatin was given as rapid infusions along with nephroprotective agents such as mannitol and magnesium sulphate (MgSO4).…”
Section: Discussioncontrasting
confidence: 69%